Pola Asuh Orang Tua di Era Digital dalam Membentuk Karakter Anak - Mukhlishah; Rahma Anjani, Adhistria; Khomsyatun Munawaroh, Annisa; Pebrianti Rahayu, Sarla; Kaffah Millati , Silma (LPPAIK Universitas Muhammadiyah Bandung, 2024)
This research discusses the role of parents in shaping children's character in the digital era. With the advancement of technology, children are more often exposed to digital devices that can affect their character development. The purpose of this study is to identify parental communication patterns and how this impacts the formation of children's character. Based on literature analysis, it was found that there are four main communication patterns applied by parents, namely consensual, pluralistic, protective, and laissez-faire patterns. Each pattern has a different influence on the development of children's characters. The conclusion of this study shows that open and educational communication from parents can help children use technology wisely and support the formation of positive character.